Welcome to America: formações imaginárias sobre imigrantes - Valgoi, Magda Karolyna da Rosa (2019)
This research aims to comprehend imaginary formations about bloke immigrant (re)produced journalistic discourse. The analysis has been made from of the cover and the reportage of the American magazine Time, it has been issued in July, second of 2018, bulkiness 192, number 1, that bring the reportage of the cover, entitled: A Reckoning After Trump’s Border Separation Policy: What Kind of Country Are We? The methodological approach has been oriented by the description of the circumstances of the magazine`s issue, that taking into account the broad and narrow`s Condition of production about the increased immigration`s flow occurred at the last two years in U.S.A; from the impact of the issue in a context with respect to immigrant in a journalist’s genre and from imaginary formations about the immigrants that this corpus (re)produce. Our assumption was that the imaginary formation (re)produced in this corpus is that the illegal immigrant represent a threat to the country. In academic terms, we embrace the discourse perspective of the French guidance, we understand that the language heterogeneity and the imaginary game form the speech and (re)produce meanings outcome. We cut out of the corpus discursive sequences in which they formulate the meanings and underpin the relationship of the power of the position that underpin the imaginary formations (FI) about the immigrant. We understand that the imaginary formations about the immigrant is composed by the rebuild regarding to the bloke citizen’s position, they challenging this bloke to be agent of the circumstances of their original country. In our analysis, we comprehend that the bloke’s image (re)produce political, social and economics consequence.